The Malay Manchester Driver Behaviour Questionnaire: A cross-sectional study of geriatric population in Malaysia. (September 2019) - Ang, Boon Hong; Chen, Won Sun; Lee, Shaun Wen
Abstract: Introduction: The Manchester Driver Behaviour Questionnaire (DBQ) can be regarded as one of the well accepted self-report measures of aberrant driver behaviour in more than 20 years. The various factor structures of DBQ had extensively been examined in past studies related to driving behaviour. The objective of this study is to examine the equivalence of the Malay DBQ factor structures in samples of older car drivers and older motorcycle riders in Malaysia. Methods: Five hundred respondents were recruited for this study. Respondents were current and former car drivers or motorcycle riders, aged 60 years and above, and resided in Malaysia. All car drivers and motorcycle riders responded to the Malay DBQ either using a paper-form or an online platform via Qualtrics. Results: All four factors in the Malay DBQ were found to be internally consistent for both car drivers sample and motorcycle riders sample. Older motorcycle riders perceived lapse items differently compared to older car drivers. Conclusions: The four-factor structures of the Malay DBQ were very similar to the original DBQ, but not identical. This study suggested declining cognitive capabilities of older people were likely to be associated with the increasing likelihood of problems with attention. Highlights: The four-factor structures of the Malay DBQ were very similar to the original British DBQ, but not identical. The alpha reliability coefficients showed the aggressive violations, ordinary violations, errors and lapses in the Malay DBQ were internally consistent. The aggressive violation items and ordinary violation items were clearly differentiated, similar to the original British DBQ, but not the lapse items. Declining cognitive capabilities of older drivers and riders were associated with the increasing problems with attention.